Profesionalitas Pendidik dalam Meningkatkan Kemampuan Membaca Al-Qur'an Peserta Didik di Pusat Pembangunan Tamadun Masyarakat Asli (PETAMA) Pahang, Malaysia - Dendy Herifan; Yusriandi; Odsisa Putera (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the professionalism of educators in improving students’ ability to read the Qur’an at PETAMA (Centre for the Development of the Indigenous Culture of Pahang), Malaysia. The professionalism of educators is regarded as a key factor in the success of Qur’anic education, as it encompasses mastery of pedagogical and professional competencies, as well as the ability to guide students in accordance with Islamic values. This study employs a qualitative approach using field research. Data collection techniques involved observation, interviews, and documentation involving educators and students at PETAMA. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that the professionalism of educators at PETAMA Pahang is of a high standard and plays a significant role in enhancing students’ ability to read the Qur’an. This is evident from their mastery of the subject matter, the application of systematic teaching methods, their patient and diligent attitude, as well as their discipline and sense of responsibility in carrying out their duties. Furthermore, the educators employ comprehensive and adaptive teaching strategies, such as the Iqra’ method, talaqqi, individualised approaches, motivational techniques, the use of teaching aids, and regular assessment. Based on these findings, it can be concluded that the professionalism of educators plays a significant role in improving pupils’ ability to read the Qur’an; therefore, efforts to enhance educators’ competence must continue so that Qur’anic education can take place effectively and sustainably.